Challenges and perspectives of user-led initiatives in post-conflict and transitional communities - Šošić, Bojan (Socialno delo, 2025)
Following the end of the war in Bosnia and Herzegovina (1992–1995), the process of reforming mental health services began, focusing on the development of community mental health centers as the backbone of dein- stitutionalized care for individuals with mental health issues. During this period, several user associations were established with the aim of amplifying the voice of service users in shaping the conditions for their improved status and full participation in society. The aim of this paper was to analyse challenges and perspectives in the development of the user-led organizations and user-led initiatives in Bosnia and Herzegovina as a post-conflict and transitional community. The authors of this paper attempted to answer exactly how and to what extent post-conflict and transitional circumstances provide an opportunity for the development of the user-led initi- atives. In searching for the answer, the case study method of a user-led organization with a twenty-five years experience was used. The findings show that in using opportunities and coping with challenges the key lies in the independence, mutual assistance skills, democratic management of the organization, involvement of all the users in the development and implementation of initiatives, openness to cooperation, inclusion in the social network and willingness to learn and share knowledge.
Keywords: community mental health; deinstitutionalisation; dezinstitucionaliazacija; duševno zdravje; fotoglas; skupnostno duševno zdravje; stigma; uporabniška združenja; user associations